Pengaruh Pemberian Alpukat Terhadap Kadar Kolesterol Total Darah Pada Mahasiswa/i Obesitas Di Fakultas Kedokteran Universitas HKBP Nommensen Medan Tahun 2019 - Syupiarni Putri Waruwu; Joseph Partogi Sibarani; Saharnauli Janna Verawaty Simorangkir (Universitas HKBP Nommensen, 2021)
Background: Cholesterol is a fat that does not dissolve easily in the blood. Most of the cholesterol in the blood is attached to specific protein carriers in the plasma in the form of lipoprotein complexes, which are soluble in water. Lipoprotein which carries cholesterol throughout the body. namely LDL (Low Density Lipoprotein) and HDL (High Density Lipoprotein). An increase in LDL in the body tends to form atherosclerosis. In contrast HDL cholesterol inhibits LDL oxidation so that atherosclerotic plaque formation does not occur. Obesity is one of the risk factors for atherosclerosis with manifestations of coronary heart disease. Handling of obesity has been done by many researchers and implemented. One ingredient from nature that serves as an alternative ingredient to lower blood cholesterol levels is avocado. Objective: To determine the effect of avocado administration on total blood cholesterol levels in the obese college students at the Medical Faculty of Nommensen HKBP University in 2019. Methods :This research is a pre-experimental study with a pre-post test design in one group. The sample was selected by purposive sampling method and obtained 20 obese students. Subjects consumed avocado juice every day for 14 days. Total cholesterol levels were measured before (day 0) and after (day 14) treatment. Results: The mean total cholesterol level of the subject's blood on the pretest examination was 188.10 mg / dL and the posttest examination was 180.05 mg / dL. There was a decrease in the average total blood cholesterol level of 8.05 mg / dl. Paired T-test showed that there was a non-significant decrease in mean total blood cholesterol level with a value of p = 0.068 (p <0.05). Conclusion: In this study there was no effect of avocado administration on total blood cholesterol levels in obese students.